Infection Temperature Affects the Phenotype and Function of Chimeric Antigen Receptor T Cells Produced via Lentiviral Technology - Jin, Xin; Lu, Wenyi; Zhang, Meng; Xiong, Xia; Sun, Rui; Wei, Yunxiong; He, Xiaoyuan; Zhao, Mingfeng (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR)-T cell therapy has become an important method for the treatment of hematological tumors. Lentiviruses are commonly used gene transfer vectors for preparing CAR-T cells, and the conditions for preparing CAR-T cells vary greatly. This study reported for the first time the influence of differences in infection temperature on the phenotype and function of produced CAR-T cells. Our results show that infection at 4 degrees produces the highest CAR-positive rate of T cells, infection at 37 degrees produces the fastest proliferation in CAR-T cells, and infection at 32 degrees produces CAR-T cells with the greatest proportion of naive cells and the lowest expression of immune checkpoints. Therefore, infection at 32 degrees is recommended to prepare CAR-T cells. CAR-T cells derived from infection at 32 degrees seem to have a balance between function and phenotype. Importantly, they have increased oncolytic ability. This research will help optimize the generation of CAR-T cells and improve the quality of CAR-T cell products.